Protection of minority shareholders / Nik Anisah Nik Omar - Nik Omar, Nik Anisah (Faculty of Law, 1987)
In Malaysia, like any other country, the establishment of companies is governed by the Companies Act which was adopted with some modification from the English Companies Act 1929.The English Companies Act 1929 was based on the Joint Stock Companies Act 1844 which laid the principle of incorporation as a basis of modern company law. Reforms have been made to the English Companies Act for quite a number of times as well as the Malaysian Companies Act. The latest amendments and certain new provisions have also been made to the Malaysian Companies Act and these were effective as from 25th April 1986.